Patient-relevant outcomes following elective, aseptic revision knee arthroplasty: a systematic review - Sabah, SA; Hedge, EA; von Fritsch, L; Xu, J; Rajasekaran, RB; Hamilton, TW; Shearman, AD; Alvand, A; Beard, DJ; Hopewell, S; Price, AJ (BioMed Central, 2023)
Background The aim of this systematic review was to summarise the evidence for the clinical effectiveness of revision knee arthroplasty (rKA) compared to non-operative treatment for the management of patients with elective, aseptic causes for a failed knee arthroplasty.